Microstructural characteristics of aluminum based composites developed by liquid metallurgyroute: an overview (2016)
The extensive potential engineering applications of Aluminium Metal Matrix Composites (AMCs) are strong motivations for researchers renewed efforts in the development and characterisation of this class of material. The importance of microstructures for AMCs characterisation is enormous for reliable interpretations of its physical, mechanical, corrosion and thermal properties. Hence, a comprehensive review is quintessential in order to have a general overview of the influence and implications of microstructural characteristics on AMCs material properties. The review shows that an improved stir casting setup provides a reliable platform for effective and efficient stirring mechanism in the production of AMCs. This improved system is capable of reducing agglomerations to the barest minimum and thus promotes homogeneous dispersion of ceramic reinforcement particles in the matrix. The nature of AMCs microstructures have specific implications to its mechanical, corrosion and wear properties. The formation of pores, pits, rough surface and ceramics particles agglomerations in AMCs microstructures are manifestations of severe corrosion of the composites in different environments. The microstructural characteristics of corroded composite samples are aggravated by the harshness of the corrosion environments and increase in the percentage weight fractions of most ceramic reinforcement particles. The type of ceramic reinforcement particles used in AMCs has been well reported in the literature to have immense influence on its microstructural characteristics. Further, the review was able to show that heat treatment is a reliable process that can be explored in enhancing the homogeneous dispersion of reinforcement particles in AMCs matrix and its overall microstructural features. This review has enriched researchers’ understanding on immense benefits of AMCs microstructural examinations and its numerous implications. It is hopeful that this will be an illuminating platform for intensifying research activities on the microstructural characterisation of AMCs. The conclusion that can be drawn from this in-depth overview is that microstructural examinations will remain one of the leading techniques for AMCs materials properties characterisation. Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Atomic Force Microscopy (AFM), Energy Dispersive Spectroscopy (EDS), X-ray Diffraction (XRD) and X-ray Fluorescence (XRF) will continue to be the domineering microstructural examinations techniques for characterising the material properties of AMCs.